2020
DOI: 10.1002/hed.26355
|View full text |Cite
|
Sign up to set email alerts
|

What is the hold up?—Mixed‐methods analysis of postoperative radiotherapy delay in head and neck cancer

Abstract: Background Delays in postoperative radiotherapy (PORT) for head and neck cancer (HNC) increase the risk for recurrence and mortality. The multifactorial nature of delays calls for an in‐depth understanding of potential contributors from the patient's and provider's perspectives. We sought to identify causes of delays in adjuvant radiotherapy initiation for HNC. Methods We performed a mixed‐methods study including patients with HNC care team members. Forty in‐depth interviews were performed (26 patients; 14 car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(46 citation statements)
references
References 42 publications
0
46
0
Order By: Relevance
“…First, the NCDB does not provide clarification regarding the reasons why patients opt to refuse PORT. While these reasons are likely multifactorial in nature, research has shown that delays in adjuvant therapy may be due to lapses in patient–physician communication, inefficiencies in care coordination, or weak social support for patients 52 . An understanding of these determinants could more clearly inform physician behavior and practice modifications.…”
Section: Discussionmentioning
confidence: 99%
“…First, the NCDB does not provide clarification regarding the reasons why patients opt to refuse PORT. While these reasons are likely multifactorial in nature, research has shown that delays in adjuvant therapy may be due to lapses in patient–physician communication, inefficiencies in care coordination, or weak social support for patients 52 . An understanding of these determinants could more clearly inform physician behavior and practice modifications.…”
Section: Discussionmentioning
confidence: 99%
“…The PN established a direct channel between patients, providers, and radiation therapy schedulers. Skyes et al identified a lack of ability to map patients in the multimodality treatment process in real time as a principal contributor to decreased PORT adherence 17 . The insertion of a PN into this expanded role in our institutional workflow served as a common denominator and central hub of communication to ease the burden of coordination from the patients and providers.…”
Section: Methodsmentioning
confidence: 99%
“…13 Analyses by various groups identify travel/transportation issues as a major cause of patients not receiving guidelineadherent radiotherapy in head and neck cancers. 14,15 In a comprehensive root cause analysis of radiotherapy initiation timing in postoperative radiotherapy in head and neck cancers, multiple factors were identified related to communication, process, and social support. Specifically identified in the social support area was the lack of transportation support as a cause of increased time to initiation of postoperative radiotherapy.…”
Section: Barrier: Travelmentioning
confidence: 99%
“…Specifically identified in the social support area was the lack of transportation support as a cause of increased time to initiation of postoperative radiotherapy. 15 Delays in receiving postoperative radiotherapy are known to negatively impact overall survival in head and neck squamous cell carcinomas. [14][15][16] Solution Employ a head and neck nurse navigator.…”
Section: Barrier: Travelmentioning
confidence: 99%
See 1 more Smart Citation